A metafísica de Isaac Newton - Oliveira, Bruno Camilo de (2012)
The general objective of this dissertation is to analyze the metaphysical aspects of "rational mechanics" of Isaac Newton, clarifying, by scientific and philosophical discourse, their main elements, with emphasis to the presence of one entity infinitely rational behind all the phenomena of nature, and to the Newton's insight as certain empiricist which, however, accepts deductions metaphysics; a philosopher-scientist. The specific objectives are detailed below: a) brief presentation of the development of modern science, since the Pre-Socratics, seeking to understand the historical conjecture that enabled the rise of Newtonian mechanics; b) presentation of the elements of scientific methodology and philosophical, aimed at comprehension of certain "Newtonian methodology", understanding how this specific methodology able to present empirical aspects, mathematics, philosophic and religious in communion; c) to understand, from the Newtonian concepts, both concerning man's role in the world as the "notional notions" of mass, space, time and movement, necessary for analysis and understanding of certain metaphysical aspects in the Newtonian physics; d) to present the Newtonian concepts related to the ether, to understand why it necessarily assumes metaphysics characteristics and mediation between the bodies; e) to present and understand the factors that lead the empiricist Newton to assume the religion in his mechanics, as well as, the existence and functions of God in nature, to object to the higher content of his metaphysics; f) to highlight the metaphysical elements of his classical mechanics, that confirm the presence of concepts like God Creator and Preserver of the natural laws; g) at last, to analyze the importance of Newton to the modern metaphysics and the legacy to philosophy of science at sec. XVII to science contemporary